FAKTOR YANG BERPENGARUH DENGAN KEJADIAN PENYAKIT GASTRITIS DI WILAYAH KERJA PUSKESMAS TANJUNG REJO - Randa Aqila Lubis; Ermi Girsang; Eka Lolita Pakpahan (Jurnal Maternitas Kebidanan, 2023)
Gastritis is a common disease of the stomach lining caused by excessive consumption of foods that stimulate stomach acid, such as spicy foods, caffeinated foods, alcohol, acids and sodas. This study aims to determine the factors that influence the incidence of Gastritis in the Working Area of Tanjung Rejo Health Center. This study uses analytical survey method with case-control approach. Sampling techniques in this study using the Slovin formula. Data analysis used univariate analysis and bivariate analysis using chi square. The results showed that there was a significant influence between age and the prevalence of gastritis in the working area of the Tanjung Rejo Health Center with a P Value of 0.044, then there was a significant influence between the Sexes with the incidence of gastritis with a p Value of 0.008, then that there was a significant influence between the family history of gastritis patients with the prevalence of gastritis with a P Value of 0.048, there was a significant influence between diet with the emergence of gastritis with a P Value of 0.000, there is a significant influence between the type of food with the incidence of gastritis p-value of 0.000, and it can be stated that there is a significant influence between age with the prevalence of gastritis with a p Value of 0.012 in the working area of Tanjung Rejo Health Center. The conclusion of this study is that there is an influence between age, sex, family history of gastritis, diet, type of food and stress with the incidence of gastritis.